Strategi Pendidikan Pesantren dalam Mitigasi Radikalisme melalui Moderasi Beragama dan Literasi Digital - Mustachsana Qurrotu 'Ainy; Rustam Ibrahim (ALSYS, 2025)
Religious extremism in pesantren has recently shown a tendency to increase, partly because digital media facilitates the dissemination of intolerant narratives among adolescents. Although previous studies have examined the kitab kuning curriculum, the influence of kyai, and santri discussion forums, research that synthesizes strategic pesantren components for mitigating radicalism remains very limited. This study aims to provide an in-depth analysis of Islamic religious education tactics in pesantren by examining curriculum, leadership, santri groups, the social environment of dormitories, and pesantren–parent relationships. A qualitative methodology with a case study design was employed, involving kyai, ustadz, and senior santri selected through purposive sampling. Data were collected through interviews, observations, and document analysis, and analyzed using a thematic analysis approach. The findings show that strengthening the turāth curriculum, the influence of kyai, the function of the Bahtsul Masail forum, the development of santri organizations, dormitory discipline, and digital literacy contribute significantly to fostering moderate understanding and ideological resilience among santri. The study introduces the concept of adaptive moderation (moderasi adaptif), which integrates pesantren traditions with the need to respond to religious issues in digital spaces. It recommends enhancing digital literacy, reinforcing family engagement, and improving pesantren administration as continuous measures to mitigate radicalization, as well as further research to develop comparative models across pesantren.